The Whole (New) World in a Cup. The Atheneum's Narwhal-and-Ivory Cup - Sigalas, Vanessa (Humboldt-Universität zu Berlin, 2018)
The Wadsworth Atheneum Museum of Art recently acquired a remarkable seventeenth-century German narwhal and ivory cup (fig. 1). It belongs to a group of at least sixteen ivory, narwhal tusk, and rhinoceros horn cups of similar style and decoration first identified by ivory expert Christian Theuerkauff in 1974 as coming from the workshop or circle of Georg Pfründt (1603–1663). This case study explores the cup’s status within the group, with the stylistic analysis leading to a new possible attribution. While this essay will focus on the cup’s complex iconography, which alludes to the New World, it will also set it in the wider context of exoticism and the early stages of globalization.